Analyze the Factors Affecting the Entrepreneurial Behavior among the Business Graduates of Bangladesh - Alam, Md. Shahbub (Indonesian Journal of Business and Entrepreneurship, 2024)
Background: Bangladesh is a densely populated country. It encompasses various problems, unemployment is one of them. Each year a large number of graduates are added to the unemployment incubator. The country's economic and social progress has been destroyed due to serious unemployment problems. This problem can be solved by arousing entrepreneurship. The successful entrepreneur plays a vital role in economic development, control of serious economic disorder, social and sustainable development challenges.Purpose: This research investigates the factors that influence the entrepreneurial behavior of Bangladeshi business graduates. Design/methodology/approach: This research is quantitative in nature. The primary data was collected from 100 business graduates of the Islamic University of Bangladesh. Various statistical analyses, such as demographic, descriptive, correlation, and regression, were used to achieve the study's aims. For measuring data popular software, SPSS was applied in this study. Findings/Result: The study found a strong positive correlation between the independent variables of general skills, risk-taking, knowledgeability, persuasive ability, persistence, and hard work, and the dependent variable of entrepreneurial behavior. Conclusion: The study proved that graduates with positive entrepreneurial behavior have a great chance of being successful entrepreneurs. This study suggests that entrepreneurship education and training programs can be used as an arm for promoting entrepreneurship.Originality/value (State of the art): The added value of this research is that it explores how entrepreneurial behavior influences one to become a successful entrepreneur in the future. Keywords: entrepreneurial behavior, business graduates, entrepreneurship, Bangladesh, ntrepreneurship education